2019
DOI: 10.1016/j.bj.2018.10.009
|View full text |Cite
|
Sign up to set email alerts
|

Effects of oral zinc supplementation on patients with noise-induced hearing loss associated tinnitus: A clinical trial

Abstract: Background Zinc plays a vital antioxidant role in human metabolism. Recent studies have demonstrated a correlation between noise-induced hearing loss (NIHL) and oxidative injury; however, no investigation has focused specifically on the subgroup of NIHL associated tinnitus patients. We aimed to evaluate the effectiveness of zinc supplementation in treating NIHL associated tinnitus. Methods Twenty patients with tinnitus and a typical NIHL audiogram (38 ears) were include… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 28 publications
1
15
0
Order By: Relevance
“…This result is also in harmony with previous reports that zinc plays a principal function in the maintenance of the integrity of Cu-Zinc SOD as a co-factor and also in regulating glutathione, which is crucial in cellular antioxidant defence mechanisms [57]. Yeh et al [4] also reported the mitigating effect of oral zinc supplementation on patients with noise-induced hearing loss associated tinnitus. Furthermore, zinc stabilises the thiol pool by protecting the sulfhydryl group, hence it shields from oxidation [58].…”
Section: Effect Of Treatments On Nitric Oxide (No) Gpx Sod and Catasupporting
confidence: 90%
See 2 more Smart Citations
“…This result is also in harmony with previous reports that zinc plays a principal function in the maintenance of the integrity of Cu-Zinc SOD as a co-factor and also in regulating glutathione, which is crucial in cellular antioxidant defence mechanisms [57]. Yeh et al [4] also reported the mitigating effect of oral zinc supplementation on patients with noise-induced hearing loss associated tinnitus. Furthermore, zinc stabilises the thiol pool by protecting the sulfhydryl group, hence it shields from oxidation [58].…”
Section: Effect Of Treatments On Nitric Oxide (No) Gpx Sod and Catasupporting
confidence: 90%
“…Documented reports show that zinc deficiency exacerbates the generation of ROS while its supplementation limits the formation of free radicals in rats [28]. Similarly, in young adults, increased levels of free radicals have been linked with impaired neurobehavioural performance, however, this impairment improves notably upon supplementation with zinc [4,29]. As such, this study aimed to evaluate the mitigative effects of kaempferol and zinc gluconate on noise-induced neurobehavioral impairments and oxidative stress in Wistar rats.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…Zinc is a structural component of superoxide dismutase which is the primary line of defense against oxidative stress. A significant improvement in the THI score was achieved in noise-induced hearing loss-associated tinnitus patients treated by zinc [ 152 ], while another study showed an adverse result in elderly tinnitus patients [ 153 ]. In any case, a Cochrane review concluded that there is no evidence of efficacy of oral zinc supplementation in adults with tinnitus [ 154 ].…”
Section: Tinnitus Management and Medicationsmentioning
confidence: 99%
“…Therefore, Yeh et al. investigate here the effectiveness of zinc supplementation in a subgroup of noise-induced hearing loss patients suffering additionally from tinnitus [21] . They conclude that although there were no improvements in objective hearing parameters, 85% of patients showed amelioration in a subjective evaluation of life quality restriction due to the tinnitus.…”
Section: Also In This Issuementioning
confidence: 99%